Dynamic and Static Overloading Induce Early Degenerative Processes in Caprine Lumbar Intervertebral Discs - Paul, Cornelis P. L.; Schoorl, Tom; Zuiderbaan, Hendrik A.; Zandieh Doulabi, Behrouz; van der Veen, Albert J.; van de Ven, Peter M.; Smit, Theo H.; van Royen, Barend J.; Helder, Marco N.; Mullender, Margriet G. (PLOS ONE, 2013)
Mechanical overloading of the spine is associated with low back pain and intervertebral disc (IVD) degeneration. How excessive loading elicits degenerative changes in the IVD is poorly understood. Comprehensive knowledge of the interaction between mechanical loading, cell responses and changes in the extracellular matrix of the disc is needed in order to successfully intervene in this process. The purpose of the current study was to investigate whether dynamic and static overloading affect caprine lumbar discs differently and what mechanisms lead to mechanically induced IVD degeneration. Lumbar caprine IVDs (n = 175) were cultured 7, 14 and 21 days under simulated-physiological loading (control), high dynamic or high static loading. Axial deformation and stiffness were continuously measured. Cell viability, cell density, and gene expression were assessed in the nucleus, inner- and outer annulus. The extracellular matrix (ECM) was analyzed for water, glycosaminoglycan and collagen content. IVD height loss and changes in axial deformation were gradual with dynamic and acute with static overloading. Dynamic overloading caused cell death in all IVD regions, whereas static overloading mostly affected the outer annulus. IVDs expression of catabolic and inflammation-related genes was up-regulated directly, whereas loss of water and glycosaminoglycan were significant only after 21 days. Static and dynamic overloading both induced pathological changes to caprine lumbar IVDs within 21 days. The mechanism by which they inflict biomechanical, cellular, and extracellular changes to the nucleus and annulus differed. The described cascades provide leads for the development of new pharmacological and rehabilitative therapies to halt the progression of DDD.